In-situ reduction-passivation synthesis of magnetic octahedron accumulated by Fe@Fe3O4-C core@complex-shell for the activation of persulfate. Issue 4 (August 2022) - Tong, Qin; Cai, Ting; Chen, Xiaotong; Xu, Peng; Ma, Yuli; Zhao, Kunfeng; He, Dannong
Abstract: The iron-based heterogeneous catalysts, especially the zero valent iron (ZVI) is an eco-friendly and cost-effective activator for persulfate (PS) excitation. However, the oxidation of surface ZVI reduces its service lifetime. Herein, a series of magnetic octahedrons accumulated by Fe@Fe3 O4 -C core@complex-shell were constructed by in-situ reduction-passivation of the MIL-101(Fe). The catalysts exhibited good activity, high stability and magnetic recyclability. The optimized Fe@Fe3 O4 -C-60 with largest proportion of active iron achieved a 100 % conversion of Rhodamine B (RhB) within 4 min and high mineralization efficiency of 667.34 % in 30 min. Moreover, Fe@Fe3 O4 -C-60 maintained its activity even after 3 times of cycling test and could be easily magnetic separation. The rate constant was 1.23 min −1 for Fe@Fe3 O4 -C-60+PS in first 3 min, which was 1.6, 5 and 323 times of Fe 0 +PS, FeSO4 +PS and Fe3 O4 +PS. Fe 0 and Fe 2+ were identified as active sites for SO4 - generating, while the carbon shell was responsible for the high stability. The synergistic effect between Fe 0 core and Fe3 O4 -C complex shell realized the sustained regeneration of active surface Fe 2+ and inhibition leaching of Fe. Highlights: ● The magnetic Fe@Fe3 O4 -C octahedrons catalysts were simply constructed by in-situ reduction-passivation of the MIL-101(Fe). ● The octahedrons were assembled by Fe@Fe3 O4 -C core@complex-shell nanoparticles. ● The relationship between active iron component and passivation temperature was revealed. ● The Fe@Fe3 O4 -C-60 catalyst exhibited high removal efficiency for RhB and reusability after three recycle test. ● The synergistic effect between Fe 0 core and Fe3 O4 -C complex shell can maintain high activity and stability of catalyst.